2021
DOI: 10.1155/2021/9945494
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure and Fractal Character of Lacustrine Oil-Bearing Shale from the Dongying Sag, Bohai Bay Basin, China

Abstract: To better understand the pore structure and fractal character of lacustrine shales and their influence on liquid hydrocarbon occurrences, in this study, a total of 29 lacustrine oil-bearing shale samples collected from the Shahejie Formation in the Dongying Sag, Bohai Bay Basin, were investigated based on nitrogen adsorption (NGA) analysis combined with TOC, Rock-Eval pyrolysis, X-ray diffraction (XRD), and field emission-scanning electron microscopy (FE-SEM) experiments. The relationships among the compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The geological setting of the study area is described and can be found in ref . To enable the petrological analysis of shale, total organic content (TOC), rock pyrolysis, and X-ray diffraction measurements were performed on the shale powder samples using the methods outlined by Zhang et al Based on the methods described by the authors in their previous papers, the SEM, LTN2GA, MICP, and NMR tests were conducted on the samples to determine their pore structures.…”
Section: Methodsmentioning
confidence: 99%
“…The geological setting of the study area is described and can be found in ref . To enable the petrological analysis of shale, total organic content (TOC), rock pyrolysis, and X-ray diffraction measurements were performed on the shale powder samples using the methods outlined by Zhang et al Based on the methods described by the authors in their previous papers, the SEM, LTN2GA, MICP, and NMR tests were conducted on the samples to determine their pore structures.…”
Section: Methodsmentioning
confidence: 99%
“…Since the pore–throat distribution controls the fluidity of fluid in shale, the mercury injection curve is appropriate for classifying the shale pore–throat system. The author’s team investigated hundreds of shale samples from Chinese shale strata, including the Shahejie Formation in Dongying Sag of the Jiyang Depression, ,,, the Qingshankou Formation in the Songliao Basin, , the Shahejie Formation in Raoyang Sag of the Jizhong Depression, , the Lucaogou Formation in Jimsar Sag of the Junggar Basin, , the Funing Formation in the Northern Jiangsu Basin, , and the Xingouzui Formation in the Jianghan Basin. , These shale samples were analyzed using high-pressure mercury intrusion testing (for the experimental method, see the literature).…”
Section: Characterization and Classification Of Shale Microscopic Por...mentioning
confidence: 99%
“…On the basis of this, the grading evaluation criteria and the lower limit of formation of shale reservoirs are established and applied to the evaluation of target reservoirs. Combined with the research results of the author’s team in recent years, ,− ,, this paper reviews and summarizes the latest progress and development trends in this area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to developments in horizontal well and hydraulic fracturing techniques, shale (including mudstone) has emerged as a commercial reservoir, and a series of achievements have been made in shale gas exploration and exploitation. , Moreover, shale oil is regarded as a future worldwide energy source because of its considerable resources and remarkable exploration breakthroughs achieved. , The assessment of shale oil resources is one of the critical steps in shale oil exploration. The pyrolysis parameter S 1 (called residual hydrocarbon in this paper) and chloroform-extractable bitumen “A” are commonly used parameters to estimate shale oil content. Rock-Eval experiments are efficient and simple and can provide many shale parameters. Therefore, S 1 is more suitable for characterizing the oil content in assessing shale oil resources .…”
Section: Introductionmentioning
confidence: 99%